Deaf sociocultural identity and experiencing symptoms of depression – a preliminary study of adult CI users with prelingual deafness - KOBOSKO, JOANNA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Joanna Kobosko, Deaf sociocultural identity and experiencing symptoms of depression – a preliminary study of adult CI users with prelingual deafness. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 275-295. Adam MickiewiczUniversity Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.25.12 Deaf sociocultural identity of the deaf is an important issue from the point of view of their psychological and social functioning. The present study was focused on people with prelingual deafness using cochlear implants (CI) demonstrating high skills in oral Polish language. The research question concerned the relation between the aforementioned identity and symptoms of depression, as well as the age, sex and age at cochlear implantation. The study included 28 prelingually deaf CI users aged between 18 and 40 and was conducted using N. Glickman’s DIDS, PHQ-9 and an information questionnaire. Deaf sociocultural identity is similar in terms of proportion of types of identities of the deaf to the results obtained in other studies, i.e. hearing and bicultural identities turned out to be predominant in the study group. The marginal identity only coexists with the presence of depression symptoms.